3D printed flexible wearable sensors based on triply periodic minimal surface structures for biomonitoring applications. (1st January 2023) - Imanian, Mohammad Ebrahim; Kardan-Halvaei, Mostafa; Nasrollahi, Fatemeh; Imanian, Ali; Montazerian, Hossein; Nasrollahi, Vahid
Abstract: Soft piezoresistive wearable conductors have led to a paradigm shift in the monitoring of human bodily motions. Cellular additively manufactured conductors are promising piezoresistive components as they offer mechanical tunability and provide controllable percolation pathways. In the present study, we engineer high surface-area cellular structures with the triply periodic minimal surface (TPMS)-based architectures to tailor their piezoresistive response for use in wearable devices. A simple and economical fabrication process is proposed, wherein a fused deposition modeling 3D printing technique is utilized to fabricate flexible thermoplastic polyurethane (TPU) cellular structures. Interconnectivity of TPMS designs enables the coating of a continuous graphene layer over the TPU internal surfaces via a facile dip-coating process. The effects of pore shape on piezoresistivity are studied in four different TPMS structures (i.e. Primitive, Diamond, Gyroid, and I-WP). Mechanical properties of sensors are evaluated through experimental procedures and computation methods using finite element analysis of the Mooney–Rivlin hyperelastic model. The piezoresistive performance of sensors exhibits durability under cyclic compression loading. Finally, we conclude that the Primitive structure offers suitable piezoresistive characteristics for sensing of walking, whereas the Diamond structure presents favorable results for respiration monitoring.